Duelo patológico y su influencia en el estado emocional de una joven de 21 años de edad del cantón Baba - Vivanco Nivela, Johanna Stefania (2021)
The purpose of this psychological intervention is to identify through Rational Emotive therapy if pathological grief influences the emotions of a 21-year-old girl from Canton Baba. It should be mentioned that the methodology used in this work is qualitative and is aimed at the scientific investigation of variables such as: pathological grief and emotions, which are exposed in the present case study, on the other hand it was considered to establish in this I work on the techniques of the TREC, which allowed the objective to be fulfilled in its entirety thanks to the therapeutic plan that arises in the psychological intervention, which is aimed at offering the patient an Individual Therapy to modify their beliefs and therefore their behavior and emotional state all this in order to provide the patient with a favorable prognosis.